Analysis of Total Debt, Revenue and Net Profit on Stock Prices of Foods And Beverages Companies on the Indonesia Stock Exchange (IDX) Period 2018-2021 - Farhan Saputra (DINASTI RESEARCH, 2022)
This study aims to determine the factors that affect the Stock Prices of Food and Beverage Companies listed on the Indonesia Stock Exchange for 2018-2021. The independent variables studied were: Total Debt, Revenue, and Net Profit, with the dependent variable being Stock Price. This study obtained 20 food and beverage companies listed on the Indonesia Stock Exchange. The sampling technique used is Simple Random Sampling to get a sample of 10 food and beverage companies. The research method used in this research is quantitative descriptive statistics. The tests used were classical assumption test, multiple linear regression analysis, coefficient of determination F test, and T-test. The company's financial statement data for 2018-2021 was obtained on the Indonesia Stock Exchange website. The company's website related to this research then processed the data using the IBM application. SPSS 27. The results of the study using the F test together show that Total Debt, Income, and Net Profit affect Stock Prices, while the T-test shows that Total Debt has no significant effect on Stock Prices, Income has no and no significant impact on Stock Prices and Earnings Net has a substantial effect on stock prices.